Childhood Somatic Complaints: Relationships with Child Emotional Functioning and Parental Factors - C. Jellesma Francine (Journal of Behavior Therapy And Mental Health, 2016)
Many schoolchildren experience somatic complaints such as headaches, abdominal pain and fatigue. The aim of the current research is to test the full model of previously found associations between negative affect and somatic complaints in parents and children. Participants were 199 children (aged 8-13, 47% boys) and their parents (aged 31-61, mostly mothers (87%). Self-reports of children and parents on worry, anxiety, depression and somatic complaints were used and parents’ reactions to children’s emotions wereassessed. The results of the study show that childhood negative affect and parental somatic complaints are positively associated with childhood somatic complaints. In turn, childhood negative affect is related to children’s worrying and to parents’ responses to children’s emotions. The more anxious or depressed children felt, the more they worried. Maladaptive parental responses (such as reprimands and discomfort) to child emotions were positively related to depression. It was also found that parents who experienced more negative affect, reported more somatic complaints and tended to report more maladaptive responses towards their children’s emotions.
Keywords: psychosomatic